A study on maintenance management of shipyard / Maznidatul Akmar Syihan Jani - Jani, Maznidatul Akmar Syihan (2006)
Shipyard industry involves mostly wide range of marine constructions, engineering and repair works. This research will be mainly on the common problems of maintenance works arise which based on three (3) case studies. It is remarkable and very astonishing to see about maintenance system at each shipyard. This research will cover maintenance organisation, maintenance policy, strategy on maintenance works and cost. Furthermore, the problem arises in maintenance works and strategy of maintenance that makes the shipyard maintenance in efficiently will also be highlighted. The research is carried out through interviews and questionnaires. Interviews are conducted with shipyard's authority and questionnaires are distributed to the staff of shipyard for data collection.